Optimizing Patient Selection for Interhospital Transfer and Endovascular Therapy in Acute Ischemic Stroke: Real-World Data From a Supraregional, Hub-and-Spoke Neurovascular Network in Germany - Stefanou, Maria-Ioanna; Stadler, Vera; Baku, Dominik; Hennersdorf, Florian; Ernemann, Ulrike; Ziemann, Ulf; Poli, Sven; Mengel, Annerose (Frontiers in Neurology, 2020)
Background: Interhospital transfer for endovascular treatment (EVT) within neurovascular networks might result in transfer of patients who will not undergo EVT (futile transfer). Limited evidence exists on factors associated with the primary patient selection for interhospital transfer from primary stroke centres (PSCs) to comprehensive stroke centers (CSCs), or EVT-workflow parameters that may render a transfer futile. Methods: A prospective, registry-based study was performed between July 1st, 2017 and June 30th, 2018, at a hub-and-spoke neurovascular network in southwest Germany, comprising 12 referring PSCs and one designated CSC providing round-the-clock EVT at the University Hospital Tübingen. Patients with acute ischemic stroke due to suspected large artery occlusion (LAO) were included upon emergency interhospital transfer inquiry (ITI). Results: ITI was made for 154 patients, 91 (59%) of whom were transferred to the CSC. Non-transferred patients (41%) had significantly higher premorbid modified Rankin scale scores (mRS) compared to transferred patients [median (IQR): 2 (1-3) vs. 0 (0-1), p<.001]. Interhospital transfer was denied due to: distal vessel occlusion (44.4%), or non-verifiable LAO (33.3%) in computed tomography angiography (CTA) upon teleconsultation by CSC neuroradiologists; limited Stroke-Unit or ventilation capacity (9.5%), or limited neuroradiological capacity at the CSC (12.7%). The CT-to-ITI interval was significantly longer in patients denied interhospital transfer [median (IQR): 43 (29-56) min] compared to transferred patients [29 (15-55), p=.029]. No further differences in EVT-workflow, and no differences in the 3-month mRS outcomes were noted between non-transferred and transferred patients (median (IQR): 2 (0-5) vs. 3 (1-4), p=.189). After transfer to the CSC, 44 (48%) patients underwent EVT. The Alberta stroke program early CT score [ORadj (95% CI): 1.786 (1.573-2.028), p<.001] and the CT-to-ITI interval (0.994 (0.991-0.998), p=.001) were significant predictors of the likelihood of EVT performance. Conclusion: Our findings show that hub-and-spoke neurovascular network infrastructures efficiently enable access to EVT to patients with AIS due to LAO, who are primarily admitted to PSCs without on-site EVT availability. As in real-world settings optimal allocation of EVT resources is warranted, teleconsultation by endovascular interventionists and prompt interhospital-transfer-inquiries are crucial to reduce the rates of futile transfers and optimize patient selection for EVT within neurovascular networks.